Mediasi Sebagai Alternatif Penyelesaian Sengketa Ekonomi Syariah - Ikhsan, Muhammad Miftahul; Mukhlas , Oyo Sunaryo; Sururie, Ramdani Wahyu (Fakultas Syariah IAIN Kerinci, 2022)
The establishment of Law Number 3 of 2006 concerning Religious Courts has increased the authority of religious courts, namely by resolving disputes from the sharia economy. Parties to the dispute can take a path that can be resolved, namely by litigation and non-litigation. There are several ways through non-litigation, such as mediation, negotiation, arbitration, and musharawah. However, the focus of this discussion is on mediation. Supreme Court Regulation Number 1 of 2016 concerning mediation procedures in court in article 1 point 1 states that mediation is one way to resolve disputes by negotiating to obtain agreement from two parties which will be assisted by a mediator. The necessity in conducting this mediation is a provision of article 10 of PERMA SES. This provision states that judges are required to seek peace first before hearing cases. Mediators in court have a vital role in the dispute resolution process from two parties Provide facilities for dialogue, neutrality, provide agreement facilities, encourage legal compliance, confidentiality, good communication skills, make agreements, stages of the mediation process, the first to fill out the form. Both parties may choose a mediator who is submitted to the judge. The initial stage in the mediation process is to provide a resume with a maximum of five days calculated to the mediator. Furthermore, the mediator mediates with negotiation material at an unlimited mediation meeting, both posita and petitum lawsuit, The mediation process takes place within thirty days calculated from the determination to carry out mediation, can be extended again for thirty days with the agreement of two parties. If within thirty days there is no sign of successful mediation, the process can be stopped immediately. If the mediation process has been carried out by the mediator and two parties, then the mediator will draw conclusions from mediation